D. G. Leahy and the Thinking Now Occurring. - McCullough, Lissa (SUNY Series in Theology and Continental Thought, 2021)
A critical introduction to the American philosopher D. G. Leahy (1937-2014), whose oeuvre sets forth a fundamental thinking in which change itself is revealed to be the very essence of reality and mind.